Factor Xa inhibitors - Perzborn, E. (Hämostaseologie, 2009)
Oral factor Xa (FXa) inhibitors are a promising alternative to current anticoagulants. This paper reviews the latest developments of oral direct FXa inhibitors and focuses on those which have been approved for the prevention of venous thromboembolism (VTE) after total hip or knee replacement or are in advanced development and have passed phase II (proof of principle) testing.The most advanced drugs are apixaban, betrixaban, edoxaban, eribaxaban, rivaroxaban, LY517717, TAK-442, and YM150. Rivaroxaban (Xarelto→) is the first direct FXa inhibitor which has recently been approved for the prevention of VTE in adult patients after elective hip or knee replacement in several countries, including the European Union and Canada. Rivaroxaban has a flat dose-dependent anticoagulant response with a wide therapeutic window and low potential for drug-drug and drug-food interactions. Rivaroxaban can be given in fixed doses without coagulation monitoring.This review describes the pharmacodynamic and pharmacokinetic profiles and the results of clinical trials with FXa inhibitors in the prevention and treatment of thromboembolic disorders.
Keywords: Factor Xa inhibitors; anticoagulants; thrombosis